Pengaruh Ideologi Etis, Personal Benefit dan Komitmen Profesional Terhadap Perilaku Manajemen Laba: Sebuah Studi Eksperimen - Ietje Nazaruddin (Universitas Muhammadiyah Yogyakarta, Indonesia, 2013)
This study aims to investigate factors that influence earnings management behavior, namely: individual ethical ideology, professional commitment on earnings management policies and personal benefits. The samples used are 261 graduate students in Indonesia as a proxy for managers and accountants. Validity and reliability testing performed before hypothesis testing using structural equation models. The results showed support for the hypothesis. Personal benefits negative effect on professional commitment and ethical ideology. Professional commitment reduce support for the practice of earnings management, as well as ethical ideology on earnings management behavior